Gugule-tois, it's the place to be! : on bodies, sex respectability and social reproduction : women' s experiences of youth on Cape Town's periphery - Mupotsa, Danai S (Gender Studies, 2016)
Initiating this research project I reflected on the subject of popular and youth culture, gender and sexuality; which then drove me to consider an analysis of dress codes and fashion in regards to notions of female respectability. Through my research process, I have often thought that I had digressed considerably; yet as I begin to narrate this story I am both surprised and amazed to find that this is in fact what I have done and thankfully, I believe I have done more. This "full circle," in thinking, doing and now presenting new knowledge was initiated in part due to a personal interest in the gendered socio-political, economic and historical meanings attached to the body surface as a whole, which I soon changed to a consideration of both the bodily surface and its interior. As stated in my research proposal, it was my contention that the female body, as opposed to the normative (or rather socially normalized) male body, has been discursively constructed as defiled, unclean and as reeking with sickness according to dominant paradigms of knowledge and social practice. Through the processes of conquest, colonialism, imperialism, racism and apartheid; black people and especially black women's bodies have suffered this violence. I have an interest in dissecting the manner by which such discourses then translate into common-sense understandings about how we both dress and perform our bodies in various social spaces; about how we begin to construct the discourse of "our culture," of good girls and social misfits, who wear the labels of "prostitute," "lesbian," or "rural," (despite their true actions or conditions) within urban spaces in contemporary Southern Africa; considering the impact of the history of a geographical apartheid, a migrant labour system, the production and re/production of notions of femininity closely associated with domesticity and the very dominant narrative of female respectability.